167k views
5 votes
The line on the graph passes through to points A (1, 3) B (7, 1)

The line on the graph passes through to points A (1, 3) B (7, 1)-example-1
User Albane
by
4.9k points

1 Answer

6 votes

Answer:

a. Gradient of line AB is
-(1)/(3)

b. The gradient of a line perpendicular to line AB is 3

c. The equation of a line passing through point (4,2) and perpendicular to AB is
y = 3x - 10

Explanation:

a.

Given

Point A (1, 3) B (7, 1)

Required

Gradient of AB

Gradient of a line is represented by m

m is calculated using the following formula


m = (y_(2) - y_(1) )/(x_(2) - x_(1))

Where the general representation of the coordinates are
A(x_1,y_1) and B(x_2,y_2)

From the given data, we have that


A(x_1,y_1) = A(1,3)


B(x_2,y_2) = A(7,1)

So, from there we know that


x_1 = 1;y_1 =3; x_2 = 7;y_2 =1


m = (y_(2) - y_(1) )/(x_(2) - x_(1)) becomes


m = (1 - 3)/(7 - 1)


m = (-2)/(6)


m = -(1)/(3)

b.

Required

Find the gradient of a line perpendicular to AB

Recall that gradient of a line is represented by m

The condition for perpendicularity is that
m_1.m_2 = -1

In (a) above, we solved the gradient of line AB to be
-(1)/(3)

Let
m_1 represent gradient of line AB

Hence,
m_1 = -(1)/(3)

Substitute
-(1)/(3) for
m_1 in
m_1.m_2 = -1

This will give


(-1)/(3) * m_2 = -1

Multiply both sides by -3


-3 * (-1)/(3) * m_2 = -1 * -3


m_2 = -1 * -3


m_2 = 3

Hence, the gradient of a line perpendicular to line AB is 3

c.

Required

Find the equation of a line passing through point (4,2) and perpendicular to AB

Equation is calculated using the gradient formula


m = (y_(2) - y_(1) )/(x_(2) - x_(1))

Since only one point is known, the formula is represented as follows


m = (y - y_(1) )/(x - x_(1))

Where
x_1 = 4; y_1 = 2

Since, the line is perpendicular to line AB, then its gradient m is equal to 3 (as calculated in b above)

So, we have
x_1 = 4; y_1 = 2; m = 3

By substitution


m = (y - y_(1) )/(x - x_(1)) becomes


3 = (y - 2)/(x - 4)

Multiply both sides by x - 4


3 * (x - 4) = (y - 2)/(x - 4) * (x - 4)


3(x - 4) = {y - 2}

Open brackets


3x - 12 = y - 2

Make y the subject of formula


3x - 12 + 2= y


3x - 10 = y

Reorder


y = 3x - 10

Hence, the equation of a line passing through point (4,2) and perpendicular to AB is
y = 3x - 10

User Kasi
by
6.3k points